2010
DOI: 10.4021/wjon2010.06.224w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Anthropometric Measures and Biomarker Changes After Neoadjuvant Therapy With Tamoxifen or Anastrozole in Postmenopausal Women With Breast Cancer

Abstract: BackgroundEpidemiological studies have reported positive associations between anthropometric measures and risk for developing breast cancers that express hormone receptors and associated mortality. However, the impact of nutritional status on the molecular response to endocrine therapy has yet to be described.MethodsBody mass index (BMI), waist circumference (WC), hip circumference (HP), and waist-to-hip ratio (WHR) were measured in patients with invasive ductal carcinoma (IDC) before and after neoadjuvant tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…An elevated plasma estrone level is strongly associated with the risk of developing the disease, and in women with estradiol or testosterone levels 20-25% above the mean values, the incidence of breast cancer is 2 to 3 times higher. 3 Besides the above-mentioned factors, Cintra et al 4 and Friedenreich 5 reported that obesity is correlated with a 30-50% higher relative risk of breast cancer in menopausal women, and that this population has a greater risk of death and recurrence. 6,7 According to Colditz et al 8 and Suzuki et al 9 , there is a positive association between high body mass index (BMI) and breast cancer risk in post-menopausal patients with hormone receptor-positive tumors.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated plasma estrone level is strongly associated with the risk of developing the disease, and in women with estradiol or testosterone levels 20-25% above the mean values, the incidence of breast cancer is 2 to 3 times higher. 3 Besides the above-mentioned factors, Cintra et al 4 and Friedenreich 5 reported that obesity is correlated with a 30-50% higher relative risk of breast cancer in menopausal women, and that this population has a greater risk of death and recurrence. 6,7 According to Colditz et al 8 and Suzuki et al 9 , there is a positive association between high body mass index (BMI) and breast cancer risk in post-menopausal patients with hormone receptor-positive tumors.…”
Section: Introductionmentioning
confidence: 99%